(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Leadership is crucial in any field. As a result, the health of the connection between management and staff is essential to the success of any business. Leadership styles in India’s Construction Industry are the focus of the present research. Appropriate management strategies and leadership are essential for the growth of India’s construction sector. This paper aims to fulfil three needs stemming from this imperative: (i) it will investigate the leadership styles employed by Indian construction industry top brass; (ii) it will analyse the connection between leadership and employee satisfaction and loyalty; and (iii) it will assess the same relationship between leadership and company loyalty. Therefore, this study focuses on the theoretical aspects and analysed those literature to assess the impact of leadership styles which have impact on occupational stress, workplace environment and job satisfaction in Indian scenario.